The Semantic Web 3rd Asian Semantic Web Conference, ASWC 2008, Bangkok, Thailand, December 8-11, 2008. Proceedings - Domingue, John; Anutariya, Chutiporn (Information Systems and Applications, incl. Internet/Web, and HCI, 2008)
This book constitutes the refereed proceedings of the 3rd Asian Semantic Web Conference, ASWC 2008, held in Bankok, Thailand, in December 2008. The 37 revised full papers presented were carefully reviewed and selected from 118 submissions. The papers address the latest results in the research and applications of Semantic Web technologies and cover topics including: scalable reasoning and logic, ontology mapping, ontology modelling and management, ontologies and tags, human language technologies and machine learning, querying, semantic Web services and semantic Web applications.